2000
DOI: 10.1016/s0925-4773(00)00303-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of retinoic acid receptor isoform transcripts in the mouse embryo

Abstract: The three murine retinoic acid receptor (RAR) genes each contain two distinct promoters which give rise to protein isoforms differing in their N-terminal regions. This study used in situ hybridization to describe the expression patterns of RARalpha1, RARalpha2, RARbeta1/3, RARbeta2/4, RARgamma1 and RARgamma2 isoform transcripts during mouse embryogenesis. RARalpha1 transcripts are widely distributed, with the exception of the central nervous system. Highest expression is found in developing muscle, pituitary g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 23 publications
2
90
0
Order By: Relevance
“…Quantitative RT-PCR (qPCR) demonstrated that Cyp26b1 is more highly expressed in the distal region of the developing limb bud at E11.5 and E12.5, as previously reported (Pennimpede et al, 2010b;Yashiro et al, 2004) (Fig. 2B) (Mendelsohn et al, 1991;Mollard et al, 2000). Large increases in Rarb expression were observed in To assess retinoid status in the limb mesenchyme, high-density primary limb mesenchymal (PLM) cultures were established from E11.5 wild-type and Cyp26b1 -/-limbs.…”
Section: Cyp26b1supporting
confidence: 81%
“…Quantitative RT-PCR (qPCR) demonstrated that Cyp26b1 is more highly expressed in the distal region of the developing limb bud at E11.5 and E12.5, as previously reported (Pennimpede et al, 2010b;Yashiro et al, 2004) (Fig. 2B) (Mendelsohn et al, 1991;Mollard et al, 2000). Large increases in Rarb expression were observed in To assess retinoid status in the limb mesenchyme, high-density primary limb mesenchymal (PLM) cultures were established from E11.5 wild-type and Cyp26b1 -/-limbs.…”
Section: Cyp26b1supporting
confidence: 81%
“…These RA reactivity zones are created by localized sources of RA in presumptive fore-and midgut and adjacent mesoderm (established by RALDH1, RALDH2, and RALDH3) combined with specific sinks of RA in the pharynx and organ primordia (such as the lung) (established by CYP26A1, CYP26B1, and CYP26C1) Blentic et al, 2003;MacLean et al, 2001;Reijntjes et al, 2005). In addition, localized endodermal expression of different rar paralogs further fine-tunes this RA signaling activity along the AP axis of the developing endoderm (Bertrand et al, 2007;Mollard et al, 2000). Finally, localized expression of rars in dorsal and ventral areas of the vertebrate endoderm may even create differential RA signaling activities along the dorsoventral (DV) body axis (Pan et al, 2007).…”
Section: Endoderm Patterning and Pharyngeal Developmentmentioning
confidence: 99%
“…RARs form functional heterodimers with the "rexinoid" receptors (RXRs), which bind to specific DNA sequences known as RA response elements (RAREs). There are three distinct RAR genes (␣, ␤, ␥), each with several isoforms that exhibit tissue-specific expression patterns (Dollé et al, 1990;Mollard et al, 2000). However, there is significant functional redundancy amongst the RARs.…”
Section: Introductionmentioning
confidence: 99%